Acupuncture Therapy for Functional Effects and Quality of Life in COPD Patients: A Systematic Review and Meta-Analysis. (20th May 2018) - Wang, Jiajia; Li, Jiansheng; Yu, Xueqing; Xie, Yang
Abstract : Objective. This study aimed to evaluate the efficacy and safety of acupuncture therapy (AT) for improving functional effects and quality of life in COPD patients. Methods. PubMed, Embase, Cochrane Library, Web of Science, Chinese Biomedical Literature Database (CBM), China National Knowledge Infrastructure (CNKI), Chongqing VIP (CQVIP), and Wanfang Data were searched. The randomized controlled trials (RCTs) evaluating the effect of AT on COPD patients were included. Primary outcome measures included six-minute walk distance (6MWD) and St. George's Respiratory Questionnaire (SGRQ). Study selection, data extraction, and risk of bias assessment were independently conducted, respectively. Statistical analysis was conducted by RevMan software (version 5.3) and Stata software (version 12.0). Results. Nineteen studies (1298 participants) were included. 6MWD improved more (MD: 47.84; 95% CI: 23.33 to 72.35;Z = 3.83, P = 0.0001 ) and effective rate was higher (OR: 2.26; 95% CI: 1.43 to 3.58;Z = 3.48, P = 0 . 0005 ) in the experimental group compared to the control group. Symptom domain scores (MD: −24.86; 95% CI: −32.17 to −17.55;Z = 6.66, P < 0.00001 ), activity domain scores (MD: −16.52; 95% CI: −22.57 to −10.47;Z = 5.36, P < 0.00001 ) and impact domain scores (MD: −13.07; 95% CI: −17.23 to −8.92;Z = 6.16, P < 0.00001 ) of SGRQ in the experimental group improved more compared to the control group. There was no significant improvement in SGRQ total scores between two groups. The improvement of FEV1 was not significant between two groups, yet subgroup analysis showed that patients treated with AT adjunctive to other treatments improved more in FEV1 (MD: 0.41; 95% CI: 0.28 to 0.54;Z = 6.01, P < 0.00001 ) compared to those treated with other treatments alone. Conclusion. AT may be effective in improving functional effects and quality of life in COPD patients. Besides, AT may also improve pulmonary function of patients with COPD. However, further high-quality RCTs are needed to confirm the efficacy and safety of AT for COPD patients.